Kampanie profrekwencyjne a postawy Polaków w kontekście wyborów do Parlamentu Europejskiego - Adamik-Szysiak, Małgorzata (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2014)
The article is a part of the reflections on the meaning of pro-attendance campaigns in the context of the increasing election absence in Poland. The considerations concentrate on the causes of electoral passivity and the steps taken by various entities (on the local, regional, national and international level) to encourage citizens to take part in elections. The period of empirical research includes two previous Polish campaigns preceding the elections to the European Parliament in 2004 and 2009. The theoretical basis of the research is provided by the concept of framing and the theory of rational choice. Special attention is paid to the original elements of communication strategies in the campaigns run by non-governmental organizations, national and international institutions. Additionally, allegations against the politicization of pro-attendance campaigns are discussed. In the light of the research results, the pro-attendance campaign in 2004 was primarily focused on informing potential voters about the voting procedure. Addressed mainly to the younger generation of voters, the campaign from 2009 revealed a qualitative change in the way of approaching and implementing the pro-attendance campaigns (use of the potential of the Internet, organization of actions integrating young voters, civic education combined with entertainment).